Evaluación de bioestimulantes posterior a la poda en el cultivo de arándanos (Vaccinium corymbosum L) var. Biloxi en las condiciones climáticas de la parroquia de San José de Chaltura, Cantón Antonio Ante - Vásquez Urbina, Marco Alexander (2023)
The present study was carried out because of the need to help fruit growers, with emphasis on blueberry cultivation, based on the use of commercial products to generate better yields and crop quality after pruning on the table. The objective of the research was to evaluate the use of biostimulants as mechanisms of physiological reactivation of sprouting in blueberry (Vaccinium corymbosum L.) var. Biloxi. Three commercial products with three different doses were evaluated: Seaweed (low dose 1 cc/l, medium dose 1,25 cc/l, high dose 1.5 cc/l), Chitosan (low dose 1.3 cc/l, medium dose 2.60 cc/l, high dose 3.9 cc/l) and Amino acids (low dose 1 cc/l, medium dose 1.50 cc/l, high dose 2 cc/l), to determine which treatment produced the best response to the variables under study: Number of stems, stem length, stem diameter, days to flowering and yield. The treatment that generated the greatest number of stems was amino acids at a high dose (2 cc/l). Similarly, the treatment that achieved the greatest stem length at 120 days after pruning was seaweed at a low dose (1 cc/l). For stem diameter at 120 days, the best treatment was based on chitosan at a medium dose (2,60 cc/l). The treatment that most shortened the days to flowering was based on amino acids at a low dose (1 cc/l). Finally, it is concluded that the use of amino acids favors the production of a greater number of stems and shortens the days to flowering, obtaining production in a shorter period in relation to the others.